Analysis of performance degradation in an electron heating dominant H-mode plasma after ECRH termination in EAST. (19th April 2018) - Du, Hongfei; Ding, Siye; Chen, Jiale; Wang, Yifeng; Lian, Hui; Xu, Guosheng; Zhai, Xuemei; Liu, Haiqing; Zang, Qing; Lyu, Bo; Duan, Yanmin; Qian, Jinping; et al.
Abstract: In recent EAST experiments, significant performance degradation accompanied by a decrease of internal inductance is observed in an electron heating dominant H-mode plasma after the electron cyclotron resonance heating termination. The lower hybrid wave (LHW) deposition and effective electron heat diffusivity are calculated to explain this phenomenon. Analysis shows that the changes of LHW heating deposition rather than the increase of transport are responsible for the significant decrease in energy confinement ( ). The reason why the confinement degradation occurred on a long time scale could be attributed to both good local energy confinement in the core and also the dependence of LHW deposition on the magnetic shear. The electron temperature profile shows weaker stiffness in near axis region where electron heating is dominant, compared to that in large radius region. Unstable electron modes from low to high k in the core plasma have been calculated in the linear GYRO simulations, which qualitatively agree with the experimental observation. This understanding of the plasma performance degradation mechanism will help to find ways of improving the global confinement in the radio-frequency dominant scenario in EAST.